2012
DOI: 10.1590/s0102-311x2012001400003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sedentary behavior and compliance with public health recommendations in Spanish adolescents: the AFINOS study

Abstract: The aims of the present study were: (i) describe patterns of sedentary behavior in Spanish adolescents; and (ii) IntroductionIn today's postmodern society, most people spend the majority of their waking hours engaging in sedentary behavior 1 . Emerging evidence shows that prolonged sedentary behavior may have a deleterious effect on health 2 . For example, excessive sedentary behavior has been associated with premature all-cause and cardiovascular disease mortality, obesity and an unfavorable cardiometaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
0
8
0
7
Order By: Relevance
“…A lower prevalence of this behavior was reported for adolescents from other countries: 32.9% on weekdays in the United States [10] and 24% and 50% among schoolchildren from Spain during the week and weekend, respectively [6]. Taken together, these findings show that the consequences of technological advances and the process of urbanization are not restricted to large urban centers but are also found in smaller and less developed cities.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A lower prevalence of this behavior was reported for adolescents from other countries: 32.9% on weekdays in the United States [10] and 24% and 50% among schoolchildren from Spain during the week and weekend, respectively [6]. Taken together, these findings show that the consequences of technological advances and the process of urbanization are not restricted to large urban centers but are also found in smaller and less developed cities.…”
Section: Discussionmentioning
confidence: 59%
“…In Brazil, a systematic review revealed the prevalence of excessive TV viewing time ranging from 11.3% to 79.5% [4]. In addition, some studies have differentiated TV viewing time during the week and on the weekend [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Data from Canada indicated alarming results with 80.6% reporting that they spent accumulatively a total of more than 2 h/day watching television, playing video games, and using a computer [36]. Martinez-Gómez et al (2012), observed in 1,724 Spanish adolescents (882 girls), aged 13 to 16 years from the Region of Madrid that over 63% were not meeting the recommendation to avoid sedentary behavior on weekdays and 87% did not comply with this recommendation on weekends [37]. These data are similar to the results obtained in the present study in a representative sample for Spanish children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Pediatrics (AAP) recommends no more than 2 hr a day of screen-based activities (e.g., TV viewing, computer games, and console games) due to the relationship between screen time and health risk (Martínez Gómez et al, 2012;Sisson et al, 2009). The American Academy of Pediatrics (AAP) recommends no more than 2 hr a day of screen-based activities (e.g., TV viewing, computer games, and console games) due to the relationship between screen time and health risk (Martínez Gómez et al, 2012;Sisson et al, 2009).…”
mentioning
confidence: 99%
“…However, to date, public health efforts have focused primarily on PA and have paid little attention to the mounting evidence to support sedentary behavior as a distinct behavior related to poor health. The American Academy of Pediatrics (AAP) recommends no more than 2 hr a day of screen-based activities (e.g., TV viewing, computer games, and console games) due to the relationship between screen time and health risk (Martínez Gómez et al, 2012;Sisson et al, 2009).…”
mentioning
confidence: 99%